How Novice EFL Teachers Regulate Their Negative Emotions - Silvia Arizmendi Tejeda; Barbara Scholes Gillings de González; Cecilio Luis de Jesús López Martínez (Asociación Colombiana de Profesores de Ingles, 2016)
This research report shares the findings that emerged from a qualitative study in which the main objective was to discover whether or not novice English as a foreign language teachers regulate their negative emotions during their initial teaching practice, and if so, how they do this. The data were collected by semi-structured interviews and observations, and analyzed by microanalysis and constant comparative analysis. The participants were five novice teachers who study English at the same university, and who were giving classes as part of their internship. The results from this research revealed that these particular novice English as a foreign language teachers use different emotional strategies to regulate their negative emotions.